Memahami Pesan Kampanye Politik Dalam Permainan Selamatkan Jakarta - Khosiah, Khosiah (Jurnal The Messenger, 2013)
Khosiah, G.331.09.0056. Understanding Political Campaign Message in Selamatkan Jakarta Game. Skripsi: Study Programme S-1 Communication Science Semarang University. The aim of the research to understand the message of political campaign in Selamatkan Jakarta Game. The theory base used in this research is the approach marks by Charles Sanders Peirce (in Littlejohn, 2009:64) defines semiosis as "a relationship among a sign, an object, and a meaning (the relationship between sign, object, and meaning)." This research used qualitative method and Semiotics analysis. The research is done by collecting data from websites related to Selamatkan Jakarta Game. It is concluded that political campaign messages in Selamatkan Jakarta Game proved to be effective with Jokowi-Ahok victory in Jakarta gubernatorial election 2012.